Musculoskeletal symptoms among sewing machine operators - Schibye, B.; Skov, T.; Ekner, D.; Christiansen, J. U.; Sjøgaard, Gisela (Scandinavian Journal of Work, Environment & Health, 1995)
' ' OBJECTIVES ': 'A longitudinal study was conducted to describe the prevalences and development of musculoskeletal symptoms among sewing machine operators in relation to age and exposure and among former sewing machine operators who changed exposure by changing occupation.' ' METHODS ': 'Musculoskeletal symptoms were assessed among 327 sewing machine operators in 1985 with the use of the standardized Nordic questionnaire. A follow-up study in 1991 showed that approximately one-third was still working as a sewing machine operator, one-third had changed occupation, and the rest were out of employment. The exposure was assessed by a questionnaire regarding the type of machine being operated, work organization, workplace design, units produced per day, and payment system.' ' RESULTS ': 'High prevalences of musculoskeletal symptoms of the neck and shoulders were found, with some associations to exposure variables such as efficiency. Initially symptom-free sewing machine operators were not at a higher risk of developing symptoms when they continued sewing during the six-year follow-up when compared with those who changed to other employment. However, symptomatic sewing machine operators who quit sewing were much more likely to be relieved of their symptoms than were symptomatic operators who continued sewing, odds ratio 3.26 [95% confidence interval (95% CI) 1.38–7.72] for 12-month symptoms and odds ratio 3.90 (95% CI 1.28–11.90) for 7-day symptoms. This trend also applied to long-lasting symptoms.' ' CONCLUSION ': 'The results demonstrate that, for many sewing machine operators, neck and shoulder symptoms are reversible and may be influenced by reallocation to other worktasks.
Keywords: exposure-response relationship; follow-up study; longitudinal study; neck symptom; questionnaire; repetitive work; shoulder symptom